The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1259/bjr.20170102
|View full text |Cite
|
Sign up to set email alerts
|

MRI appearance of invasive subcentimetre breast carcinoma: benign characteristics are common

Abstract: Benign characteristics are present in most invasive cancers ≤5 mm. Small cancers on MRI may need to demonstrate growth to determine need for biopsy. Advances in knowledge: MR lesion characteristics may not be helpful in determining whether small lesions on MR are benign or malignant. However, as 97% of cancers in our study showed interval change when a prior MR for comparison was available, new lesions or increasing size should lead to consideration of biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…With advancements in hardware and software, the spatial resolution of MRI has improved, allowing not only the detection but also the morphologic characterization of small enhancing lesions [19]. Meissnitzer et al [13] showed that sub-centimeter invasive breast cancers often present with benign morphologic features such as persistent enhancement (30%) and high T2 signal (17%). Raza et al [20] demonstrated that breast cancers smaller than 5 mm tend to present with circumscribed margins (71%), benign shape (67%), and benign kinetic characteristics (41%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With advancements in hardware and software, the spatial resolution of MRI has improved, allowing not only the detection but also the morphologic characterization of small enhancing lesions [19]. Meissnitzer et al [13] showed that sub-centimeter invasive breast cancers often present with benign morphologic features such as persistent enhancement (30%) and high T2 signal (17%). Raza et al [20] demonstrated that breast cancers smaller than 5 mm tend to present with circumscribed margins (71%), benign shape (67%), and benign kinetic characteristics (41%).…”
Section: Discussionmentioning
confidence: 99%
“…Meissnitzer et al [ 13 ] showed that sub-centimeter invasive breast cancers often present with benign morphologic features such as persistent enhancement (30%) and high T2 signal (17%). Raza et al [ 20 ] demonstrated that breast cancers smaller than 5 mm tend to present with circumscribed margins (71%), benign shape (67%), and benign kinetic characteristics (41%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schlossbauer et al summarized MRI dynamic and morphologic criteria in a diagnostic score and they concluded that score differences between benign and malignant lesions were reduced in lesions smaller than 1 cm in size. Other work indicates that cancers less than 1 cm become more obviously malignant as they enlarged, and that cancers less than 5 mm had benign characteristics . As MRI screening is becoming more widespread for selected high‐risk populations, it has been noted in this population that the majority of invasive carcinomas detected via this route are smaller than 1 cm in size .…”
mentioning
confidence: 99%
“…Other work indicates that cancers less than 1 cm become more obviously malignant as they enlarged, and that cancers less than 5 mm had benign characteristics. 8 As MRI screening is becoming more widespread for selected high-risk populations, it has been noted in this population that the majority of invasive carcinomas detected via this route are smaller than 1 cm in size. 9 Lesions regarded as suspicious (categorized as Breast Imaging-Reporting and Data System [BI-RADS] 4 or 5) are usually recommended for biopsy, 10 and since a higher percentage of smaller lesions are known to be benign, 11 this can potentially lead to a large number of negative biopsies, and thus a low positive predictive value.…”
mentioning
confidence: 99%